How should COPD patients exercise during respiratory rehabilitation? Comparison of exercise modalities and intensities to treat skeletal muscle dysfunction. Issue 5 (28th April 2005) - Puhan, M A; Schünemann, H J; Frey, M; Scharplatz, M; Bachmann, L M
Abstract : Background: Physical exercise is an important component of respiratory rehabilitation because it reverses skeletal muscle dysfunction, a clinically important manifestation of COPD associated with reduced health-related quality of life (HRQL) and survival. However, there is controversy regarding the components of the optimal exercise protocol. A study was undertaken to systematically evaluate and summarise randomised controlled trials (RCTs) comparing different exercise protocols for COPD patients. Methods: Six electronic databases, congress proceedings and bibliographies of included studies were searched without imposing language restrictions. Two reviewers independently screened all records and extracted data on study samples, interventions and methodological characteristics of included studies. Results: The methodological quality of the 15 included RCTs was low to moderate. Strength exercise led to larger improvements of HRQL than endurance exercise (weighted mean difference for Chronic Respiratory Questionnaire 0.27, 95% CI 0.02 to 0.52). Interval exercise seems to be of similar effectiveness as continuous exercise, but there are few data on clinically relevant outcomes. One small RCT which included patients with mild COPD compared the effect of high and low intensity exercise (at 80% and 40% of the maximum exercise capacity, respectively) and found larger physiological training effects from high intensity exercise. Conclusions: Strength exercise should be routinely incorporated in respiratory rehabilitation. There is insufficient evidence to recommend high intensity exercise for COPD patients and investigators should conduct larger high quality trials to evaluate exercise intensities in patients with moderate to severe COPD.